Soft skills and teacher performance at the higher level of education - Rodriguez Siu, Jenny Liliana (2021)
After the investigation and interpretation of previous studies, theories and concepts concerning the research topic, in the following sections of this review paper, it is intended to develop, in a conceptual and analytical way, soft skills in education; the dimensions of soft skills, according to Daniel Goleman; soft skills in the higher level teacher; teaching performance; the evaluation of teaching performance at the higher level; and, finally, the importance of soft skills for the performance of the university teacher.